(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2017)
This research note outlines ideas and maps out the critical context of the author’s current research project entitled “It’s More Fun in the Philippines: Positive Affects and the Post-Colonial Condition.” It also engages with recent literature from the expanding field of critical happiness studies. This project, envisioned to be a book-length study, explores the enabling as well as the obstructive capacities of so-called positive affects in imagining and realising an affirmative and sustainable cultural and socio-political practice within conditions of postcoloniality. In the process, it bridges several disciplines – in particular, Postcolonial Studies, Affect Theory, Critical/Cultural Theory and Gender Studies – and also aims to analyse a variegated body of philosophy, literature and cinema.